REPURPOSING EXISTING MEDICATIONS FOR CHRONIC PAIN MANAGEMENT: A COMPREHENSIVE REVIEW OF MECHANISMS, EFFICACY, AND FUTURE DIRECTIONS - Vasconcelos, Elena Antunes de; Coradin, Julia; Caiado, Fernanda Leal; Destefani, Afrânio Côgo; Destefani, Vinícius Côgo (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2024)
Chronic pain is a major global health issue, affecting around 20% of the adult population in Western countries. Current treatment options often prove inadequate and carry significant side effects, particularly with opioids. Developing new analgesics faces challenges due to difficulties in translating preclinical findings to human outcomes, resulting in clinical trial failures. Considering these obstacles, drug repurposing has emerged as a viable strategy to find new therapeutic options for chronic pain management. This approach investigates existing approved or previously failed drugs for new indications, bypassing the lengthy and costly traditional drug development process. This narrative review provides a comprehensive and in-depth overview of drug repurposing in chronic pain management, examining mechanisms of action, efficacy, and future directions for research and clinical application, ensuring that you, as healthcare professionals, researchers, and individuals involved in chronic pain management, are well-informed and knowledgeable in this area.